2021
DOI: 10.1016/j.bbih.2021.100309
|View full text |Cite
|
Sign up to set email alerts
|

Are alterations in estradiol, cortisol, and inflammatory cytokines associated with depression during pregnancy and postpartum? An exploratory study

Abstract: Background Pregnant veterans are a subpopulation known to be at elevated risk of developing mental health symptoms, such as depression and suicidal ideation. Inflammation has been associated with depression, specifically during the perinatal period. Critical changes in estradiol, cortisol, and inflammatory cytokines are necessary for the progression of a healthy pregnancy, which are then rapidly altered in the postpartum period. We explored changes in estradiol, cortisol, and pro-inflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Because cortisol is associated with immunosuppression in pregnancy, it was unlikely that both our hypotheses would have been, simultaneously, true, that pica would be correlated with both higher cortisol and higher inflammation; therefore, our study may distinguish between these two possibilities. These two physiological states tend not to co‐exist, although some studies have found no correlation between maternal prenatal cortisol and inflammation (Nazzari et al, 2020; Szpunar et al, 2021) and both have been associated with prenatal mood disorders (Christian et al, 2009; Haeri et al, 2013; Osborne et al, 2019; Schweizer‐Schubert et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Because cortisol is associated with immunosuppression in pregnancy, it was unlikely that both our hypotheses would have been, simultaneously, true, that pica would be correlated with both higher cortisol and higher inflammation; therefore, our study may distinguish between these two possibilities. These two physiological states tend not to co‐exist, although some studies have found no correlation between maternal prenatal cortisol and inflammation (Nazzari et al, 2020; Szpunar et al, 2021) and both have been associated with prenatal mood disorders (Christian et al, 2009; Haeri et al, 2013; Osborne et al, 2019; Schweizer‐Schubert et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies ( Ahn and Corwin, 2015 ; Nagayasu et al, 2021 ) did not find the correlation between IL-6 levels and the scores of Edinburgh Postpartum Depression Scale (EPDS), depressive symptoms, or stress variables. In an exploratory study among postpartum veterans ( Szpunar et al, 2021 ), the researchers found that elevated IL-1β and tumor necrosis factor-α (TNF-α) might have a positive correlation with the severity of depressive symptom. And the high level of IL-1β was also related to suicidal thoughts during pregnancy ( Szpunar et al, 2021 ).…”
Section: Inflammatory Pathophysiological Mechanisms In Postpartum Dep...mentioning
confidence: 99%
“…In an exploratory study among postpartum veterans ( Szpunar et al, 2021 ), the researchers found that elevated IL-1β and tumor necrosis factor-α (TNF-α) might have a positive correlation with the severity of depressive symptom. And the high level of IL-1β was also related to suicidal thoughts during pregnancy ( Szpunar et al, 2021 ). Similarly, other studies showed that uric or plasmic IL-1β was increased in mothers with depressive symptoms or high scores of EPDS (≥13) ( Corwin et al, 2008 ; Sha et al, 2022 ).…”
Section: Inflammatory Pathophysiological Mechanisms In Postpartum Dep...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of objective measures, such as biomarkers, was identified as an important tool to help identify women at risk for postpartum depression ( Fransson, 2021 ) . In line with these suggestions, Szpunar et al. (2021) explored the complex relationships between estradiol, inflammatory markers (e.g., interleukin (IL)-1β and IL-6), cortisol, and depressive symptoms across both pregnancy and the postpartum period.…”
Section: Introductionmentioning
confidence: 99%